Efficacy of Metabolic and Psychological Screening for Mood Disorders Among Children With Type 1 Diabetes - Butwicka, Agnieszka (American Diabetes Association, 2012)
OBJECTIVE: To compare the diagnostic accuracy and time expenditure of screening models based on glycated hemoglobin (HbA(1c)) level and psychometric measures for mood disorder (MD) among children with type 1 diabetes. RESEARCH DESIGN AND METHODS: With semistructured clinical interviews (Schedule for Affective Disorders and Schizophrenia for Children–Present and Lifetime version, 120 min/patient) as a reference for diagnosing MD, including major depressive disorder (MDD), we tested 163 subjects, aged 8 to 18 years, with type 1 diabetes. We evaluated four screening approaches: 1) Children’s Depression Inventory (CDI) at 30 min/patient, 2) HbA(1c) level, 3) HbA(1c) level plus CDI, and 4) HbA(1c) level plus Children's Depression Rating Scale (CDRS) at 40 min/patient. These tests were conducted with all participants, and the total time expenditure for all four approaches was calculated as the total time needed to implement successfully the screening for MD or MDD in the center. RESULTS: HbA(1c) performed on par with individual psychometric tests in diagnosing MD or MDD. The HbA(1c) plus CDRS model was the best screening procedure for both MD and MDD, with diagnostic thresholds for HbA(1c) established at 8.7% and 9.0%, respectively. Cutoff points for CDRS assessed after filtering by HbA(1c) were 26 (MD) and 30 (MDD) points. Center-wide application of this procedure would result in an 83% reduction of the examination time necessary for the psychiatrist for MD screening and a 91% reduction for MDD screening, as compared with standard screening with CDI. CONCLUSIONS: Use of HbA(1c) level followed by CDRS is a time-efficient procedure to screen for MD in children with type 1 diabetes.